Effectiveness of Online Tax Services Via www.pajakonline.jakarta.go.id - Mulatsih, Trisni Dwi (Data : Journal of Information Systems and Management, 2023)
Online tax services through the BAPENDA website are one of the policies of the Directorate General of Taxes (DGT) so that taxpayers can complete their taxes electronically. Based on Circular number SE – 42 /PJ/2017, online tax service is an electronic system provided by the Directorate General of Taxes or other parties appointed by the Directorate General of Taxes to be used by taxpayers who want to manage their taxes electronically through DJP Online and Electronic service provider. In compiling this thesis, the author used descriptive research methods. The results show that online tax services hrough www.pajakonline.jakarta.go.id are the right strategy to increase local tax revenues because this service really helps taxpayers save time and costs, learn features on the website, reduce paper use, and reduce mobility during the Covid-19 pandemic. However, there are still internal barriers in terms of technology, namely inaccessibility of the website, network errors, and unstable electricity, while external obstacles include the lack of understanding and knowledge of taxpayers about TI. Efforts that have been made by the tax authority are conducting campaigns to the public directly or through the Bapenda website on how to use online tax services. Tutorials such as how to register and how to apply for a tax deduction online have also been created. To further improve online services, campaigns should be increased and counseling should also be provided so that taxpayers are more aware and better understand online tax services.